Giardia intestinalis: aphidicolin influence on the trophozoite cell cycle - Hofštetrová, Klára; Uzlíková, Magdalena; Tůmová, Pavla; Troell, Karin; Svärd, Staffan G; Nohýnková, Eva (Experimental parasitology, 2010)
This study is a thorough examination of the effects of the DNA polymerase inhibitor aphidicolin on the nuclear cycle and cell cycle progression characteristics, as well as their reversibility, in Giardia intestinalis. Giardia trophozoites are arrested in the G1/S-junction after aphidicolin treatment according to their DNA content. However, cell growth continues and trophozoites arrested with aphidicolin resemble cells in the G2 phase and trophozoites in ageing cultures. Extensive treatment with aphidicolin causes side effects and we detected positive signals for phosphorylated histone H2A, which, in mammalian cells, is involved in a signalling pathway triggered as a reaction to double stranded DNA breaks. These results suggest that aphidicolin causes dissociation of the nuclear and cytoplasmic cycles, a phenomenon that has also been described for other inhibitors in mammalian cell lines. Thus, if aphidicolin is used for synchronization of Giardia trophozoites, this fact must be accounted for, and treatment with aphidicolin must be minimal. Copyright 2009 Elsevier Inc. All rights reserved.
Keywords: DNA-dependentní DNA-polymerasy; fluorescenční protilátková technika; Phosphorylation; mitotický index; Bromodeoxyuridine; afidikolin; histony; fosforylace; Cell Cycle; cyklin B; Aphidicolin; protozoální DNA; inhibitory syntézy nukleových kyselin; Time Factors; DNA, Protozoan; DNA-Directed DNA Polymerase; trofozoiti; časové faktory; Cyclin B; bromodeoxyuridin; DNA Replication; Nucleic Acid Synthesis Inhibitors; Giardia lamblia; Flow Cytometry; replikace DNA; Histones; Mitotic Index; inhibitory enzymů; poškození DNA; DNA Damage; průtoková cytometrie; Fluorescent Antibody Technique; Enzyme Inhibitors; buněčný cyklus; Trophozoites